1164. Epidemiology of Cryptococcal Infections in Non-HIV Patients: A 20-year Single Center Experience. (31st December 2020) - Kumar, Rebecca Nirmal; Nam, Hannah; Roberts, Scott C; Penugonda, Sudhir; Angarone, Michael; Stosor, Valentina
Abstract: Background: Cryptococcus has a worldwide distribution, with C. neoformans and C. gattii being two of the most common species causing disease. Despite advances in therapy, disseminated infection often results in significant morbidity and mortality. Methods: We conducted a single center retrospective cohort study over a twenty-year period spanning from January 2000 through May 2020 to determine epidemiology and outcomes of non-HIV-associated cryptococcosis at Northwestern Memorial Hospital. Cases were identified by positive culture data or positive cryptococcal antigen in the serum or cerebrospinal fluid (CSF). Epidemiology of risk factors, morbidity, and mortality was evaluated. Results: 81 cases were identified of which, 67 had Cryptococcus spp isolated from culture and the remaining patients diagnosed by cryptococcal antigen and/or histopathology. The cohort was primarily Caucasian (56.8%, n=46) and male gender (67.9%, n=55), with a median age of 59.5 (IQR: 52.75-66.25) years old. Common predisposing conditions were diabetes (37%, n=30), chronic kidney disease (34.6%, n=28), and liver disease (28.4%, n=23). Solid organ transplant recipients and use of immunosuppression accounted for, respectively, 32.1% (n=26) and 29.6% (n=24) of the cohort. Sites of infection include lung (65.4%. n=53), central nervous system (33.3%, n=27), blood (30.9%, n=25), peritoneum (6.2%, n=5), musculoskeletal (2.5%, n=2), and prostate (1.2%, n=1). Mean opening pressure on lumbar puncture was 25.3 mmHg (range: 9 -52 mmHg). In hospital mortality at time of diagnosis was 27.2% (n=22), and mortality at 12 months post diagnosis was 51.9% (n=42). Conclusion: At our center, those with cryptococcosis commonly had risk factors such as immunosuppression either secondary to solid organ transplant or otherwise. Morbidity and mortality remain high. Disclosures: Sudhir Penugonda, MD, MPH, AbbVie, Inc. (Employee, Other Financial or Material Support, ownership and/or investment interests) Michael Angarone, DO, Abbvie (Other Financial or Material Support, Data Safety Monitoring Board)Allergan (Speaker's Bureau)